Preservation of Olfaction after Unilateral Endoscopic Approach for Resection of Esthesioneuroblastoma - Wessell, Aaron; Singh, Ameet; Litvack, Zachary (Journal of Neurological Surgery Reports, 2014)
Objectives We present a case of olfactory preservation after a unilateral transcribriform transethmoidal endoscopic resection of esthesioneuroblastoma. We also discuss the oncologic results of endoscopic and transcranial approaches and describe the potential benefits and limitations of an endoscopic approach.Setting Single academic medical center.Participant and Design The clinical course of a 28-year-old patient who underwent endoscopic en bloc resection of esthesioneuroblastoma through a unilateral transcribriform transethmoidal approach was reviewed.Results Imaging demonstrated a left-sided nasal mass with cribriform plate involvement (Kadish C). Intraoperatively, the left olfactory bulb and epithelium were sacrificed. Negative frozen sections were obtained from the right olfactory epithelium and dura surrounding the right olfactory bulb. Reconstruction was performed using a multilayered closure of fascia, rigid buttress, and nasoseptal flap. Histology was consistent with esthesioneuroblastoma. Postoperative clinical evaluation, endoscopy, and magnetic resonance imaging demonstrated no evidence of residual or recurrent tumor at 18 months. The UPSIT smell testing revealed normal olfaction preoperatively, moderate microsomia at 3 months postoperatively, and mild microsomia at 18 months postoperatively.Conclusions Endoscopic resection of esthesioneuroblastoma has demonstrated similar oncologic control while reducing postoperative morbidity and mortality over transcranial approaches. This case reveals the potential to preserve olfaction while achieving en bloc endoscopic resection of early stage esthesioneuroblastoma.
Keywords: endoscopy; esthesioneuroblastoma; skull-base; olfactory preservation; craniofacial